Expression of Bcl-2 and clinicopathological variables in salivary glands mucoepidermoid carcinoma - Abdulhussain, Mustafa Mohammed (International Journal of Health Sciences, 2022)
Objective: Mucoepidermoid carcinoma (MEC) has several diagnostic, biological, and histopathological manifestations, each of which presents issues and difficulties in terms of diagnosis, grading, classification, and therapy. The goal of this study was to find out how the anti-apoptotic protein Bcl2 was expressed in salivary gland (SG) MEC and how it related to a number of clinicopathological factors. Methods: The present study comprised 30 MECs of the SG lesions that were histopathologically diagnosed. The immunohistochemistry method was used to determine Bcl-2 expression. The spss software version 20.0 was used to find a link between Bcl-2 expression and clinical and histological features. Results: The patients’ average age was 49.93 years, and MEC of SGs was more common in females. The palate was the most commonly involved area, accounting for 13 (43.3%) of cases, followed by the parotid glands, which accounted for 8 (26.7%). High-grade tumors accounted for 14 (46.7%) of the cases, whereas mild-grade tumors accounted for 10 (33.3%) and moderate-grade tumors accounted for 6% (20.0%). Bcl-2 immunostaining was associated with gender (P = 0.047), there was also a significant (P = 0.002) difference in tumor grade and age groups. Furthermore, no significant relationships between Bcl-2 expression and the other variables were discovered. Conclusion: Gender and age affect MEC tumor aggressiveness and grade. High-grade MEC tumors expressed Bcl-2 strongly and moderately, whereas low-grade tumors expressed it moderately. Bcl-2 may predict MEC tumor aggressiveness. MEC therapy may target Bcl-2.